Risk Factors Related to New-Onset Diabetes after Renal Transplantation in Patients of a High Complexity University Hospital in Colombia, 20 Years of Experience - Guillermo E. Guzmán; Angela M. Victoria; Isabella Ramos; Alejandro Maldonado; Eliana Manzi; Juan F. Contreras-Valero; Liliana Mesa; Johanna Schweineberg; Juan G. Posada; Jorge I. Villegas; Luis A. Caicedo; Carlos E. Durán (International Journal of Endocrinology)
Introduction. New-onset diabetes after transplantation (NODAT) is associated with immunosuppression. Its complications can negatively influence patients’ quality of life, which is why it is important to study the associated risk factors and expand the possible therapies in this particular group of patients. Materials and methods. Case-control study nested in a retrospective cohort. It included patients who received kidney transplantation at the high complexity University Hospital Fundación Valle del Lili in Cali, Colombia, between 1995 and 2014. Two controls were assigned for each case, depending on the type of donor and the date of the surgery. Information was collected from clinical records and the institutional TRENAL registry. We carried out a descriptive analysis of the selected variables and identified the risk factors with conditional logistic regression. Results. 122 cases were identified to which 224 controls were assigned. The median age was 44 years (IQR: 34–55), and 54% were men. Having >50 years of age at the time of transplantation (OR: 3.18, 95% CI: 1.6−6.3, p = 0.001), body mass index >30 kg/m2 (OR: 3.6, 95% CI: 1.3−9.7, p = 0.010) and being afro-descendant (OR: 2.74, 95% CI: 1.1−6.5, p = 0.023) were identified as risk factors for the development of NODAT. Pretransplant fasting plasma glucose >100 mg/dl (OR: 2.9, 95% CI: 1.4−6.4, p = 0.005) and serum triglycerides >200 mg/dl (OR: 2.5, 95% CI: 1.4−4.4, p = 0.002) were also reported as independent risk factors. Conclusion. We ratify some risk factors for the development of this important disease, which include certain modifiable characteristics. Interventions aimed at changes in lifestyle could be established in a timely manner before transplant surgery.